Functional fitness of people over 65 participating in physical activities organized by the Universities of the Third Age and Seniors’ Clubs in South-Eastern Poland - Szeremeta, Katarzyna; Grzywacz, Renata; Czarny, Wojciech (Anthropological Review, 2020)
The subject of the research was to assess the level of functional physical fitness of people aged 65 and over, taking into account the sex of the respondents, and to estimate the direction of changes in the functional physical fitness of the respondents as a result of participation in programmed physical activities of a University of the Third Age. The research on the level of functional physical fitness was carried out both among men and women aged 65 and over (104 men – 29% of the respondents and 251 women – 71% of the respondents), in total 355 people who are members of the Universities of the Third Age in Rzeszów, Mielec, Jasło, Zamość, and Seniors’ Clubs in Rzeszów, Stalowa Wola, Przemyśl, Krosno and Lubaczów. The Functional Senior Fitness Test by Rikli and Jones (1999) was used to objectively analyse the level of functional physical fitness in the study group. The individual tests of the Functional Senior Fitness Test give the opportunity to assess the muscle strength of the lower and upper body, flexibility in the upper and lower body areas, agility and dynamic balance as well as the aerobic endurance of the senior citizen.The research procedure assumed two studies to assess the level of functional physical fitness of people over 65 using the Functional Senior Fitness Test among seniors who are members of Universities of the Third Age participating in physical activities. Study 2 was conducted 6 months after study 1. In order to obtain reliable and credible results of individual tests and to maintain similar conditions for all participants, study 1 was conducted at the University of the Third Age at the beginning of the winter semester, and study 2 at the end of the first half of the academic year. The number of respondents was n = 86.Men showed statistically significantly higher results in muscle strength in upper and lower parts of the body and aerobic endurance, women in flexibility of upper and lower parts of the body. Regular participation in physical activities among people over 65 has a significant statistical impact on the achievement of higher results in individual motor skills.Sex significantly differentiates the level of functional physical fitness in selected age groups. A significantly higher level of functional physical fitness was presented by men in the test of muscle strength in in upper and lower parts of the body, agility and dynamic balance, and aerobic endurance, while women showed higher results in flexibility of upper and lower parts of the body.The analysis of the results of the preliminary (study 1) and repeated (study 2) functional fitness level allows us to find significant differences in the results of the Functional Senior Fitness Test. It is worth noting that the regular participation in programmed physical activities organized at U3A contributed to an improvement in individual motor skills, such as the strength of the lower and upper body and aerobic endurance.